A Survey Study on Public Attitudes Toward Gaming Disorder - Reer, Felix (2025)
The World Health Organization’s decision to include addictive game use (“gaming disorder”) in the International Classification of Diseases was the subject of controversial scientific debates (e.g., Aarseth et al., 2017; Rumpf et al., 2018; for an overview, see Reer & Quandt, 2021). However, knowledge is scarce on how addictive game use is perceived outside of academic circles (Schatto-Eckrodt et al., 2020). The current study aimed to fill this research gap by interviewing a stratified German sample (N = 1,075) on their attitudes toward the topic. We found that critical views about games and their addiction potential are rather common among the German general population. Further, we found evidence that many participants overestimated the number of players affected by gaming disorder. Regression analyses showed that age, gender, and gaming experience play a role in how individuals think about risks associated with game use. Interestingly, having heard about the topic in the media was associated with more critical attitudes and higher presumed prevalence rates. More exchange between scholars and the wider public is needed to increase knowledge on the topic. Further, media reports on gaming disorder should cover the latest research findings and the opposing views of scientists.